Closed mouth method with dynamic and muco compressive impression on upper and lower jaw flat ridges for aid full denture retention - Utari Kresnoadi; Rostiny Rostiny (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
A patient with flat ridge difficult to have retentive complete denture. The aim of this paper is to describe the combination of impression using closed mouth technique with dynamic and muco compressive material. In this case, the combination technique of dynamic impressive material and muco compressive material with closed mouth method on patient with upper and lower jaw flat ridges. The patient has made complete denture 10 times but not satisfied. The treatment of upper and lower flat ridges using this technique resulted retentive, stable and comfortable denture.